ウォリスの公式

ウォリスの公式

\[ \prod_{k=1}^{\infty}\left(\frac{(2k)^{2}}{(2k-1)(2k+1)}\right)=\frac{\pi}{2} \]

\begin{align*} \prod_{k=1}^{\infty}\left(\frac{(2k)^{2}}{(2k-1)(2k+1)}\right) & =\prod_{k=1}^{\infty}\left(\frac{(2k-1)(2k+1)}{(2k)}\right)^{-1}\\ & =\prod_{k=1}^{\infty}\left(\frac{(2k)^{2}-1}{(2k)^{2}}\right)^{-1}\\ & =\frac{\pi}{2}\left\{ \frac{\pi}{2}\prod_{k=1}^{\infty}\left(1-\frac{\left(\frac{1}{2}\right)^{2}}{k^{2}}\right)\right\} ^{-1}\\ & =\frac{\pi}{2}\sin^{-1}\left(\frac{\pi}{2}\right)\qquad,\qquad\sin(\pi z)=\pi z\prod_{k=1}^{\infty}\left(1-\frac{z^{2}}{k^{2}}\right)\\ & =\frac{\pi}{2} \end{align*}

ページ情報

タイトル

ウォリスの公式

URL

https://www.nomuramath.com/rszzqz7i/

SNSボタン